2018
DOI: 10.1038/s41398-018-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to TiO2 nanoparticles in mice causes behavioral deficits with relevance to autism spectrum disorder and beyond

Abstract: Environmental factors are involved in the etiology of autism spectrum disorder (ASD) and may contribute to the raise in its incidence rate. It is currently unknown whether the increasing use of nanoparticles such as titanium dioxide (TiO2 NPs) in consumer products and biomedical applications may play a role in these associations. While nano-sized TiO2 is generally regarded as safe and non-toxic, excessive exposure to TiO2 NPs may be associated with negative health consequences especially when occurring during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 83 publications
0
28
1
Order By: Relevance
“…The study also showed that the 4–8 nm TiO 2 NPs were not able to cross the placenta in an ex vivo perfusion model [ 34 ], whereas PS NPs up to 240 nm have been shown to reach the fetal circuit [ 43 ] in a similar perfusion study. In agreement, in pregnant mice, 5 nm TiO 2 did not cross the placenta [ 79 ], while PS NPs up to 500 nm could be observed in various organs of fetuses [ 27 ]. Moreover, Kloet et al observed a difference in translocation behavior of PS NPs with a similar size and surface charge but acquired from different manufactures [ 28 ].…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…The study also showed that the 4–8 nm TiO 2 NPs were not able to cross the placenta in an ex vivo perfusion model [ 34 ], whereas PS NPs up to 240 nm have been shown to reach the fetal circuit [ 43 ] in a similar perfusion study. In agreement, in pregnant mice, 5 nm TiO 2 did not cross the placenta [ 79 ], while PS NPs up to 500 nm could be observed in various organs of fetuses [ 27 ]. Moreover, Kloet et al observed a difference in translocation behavior of PS NPs with a similar size and surface charge but acquired from different manufactures [ 28 ].…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, radioactivity detected in fetuses was lower at later stages compared with earlier stages of gestation (0.2% at GD11 and 0.04% at GD18), which can be explained by the lack of a developed placenta during early gestation [ 87 ]. Seven animal studies did not find evidence of maternal-fetal transfer of engineered NPs [ 56 , 63 , 68 , 72 , 77 , 79 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations